(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The process where pristine graphite is subjected to a solvent treatment seems simple and scalable and has attracted the attention of researchers over many years. However, for successful exfoliation, overcoming the van der Waals attractions between the adjacent layers of graphite is necessary. Over time, several methods have been created to overcome the attraction between layers. Graphene’s liquid phase exfoliation (LPE) occurs due to the strong interactions between the solvent molecules and the basal planes of graphite, overcoming the energetic resistance to exfoliation and subsequent dispersion. Ultra sonication used for exfoliation can produce single or few layered graphene flakes. During sonication the sound waves propagate through liquid medium in alternating high- and low-pressure cycles, strong mechanical and thermal energy released by acoustic cavitation results in splitting up large particles into fine ones and dispersing them. Simultaneous insertion of solvent and/or intercalation molecules in between the graphite layers takes place supporting graphite separation into graphene layers. ; The dispersion capacity of graphene flakes depends on how appropriate the solvent properties are to the corresponding properties of graphene, such as surface tension, Hildebrand, and Hansen solubility parameters. Only certain solvents can disperse graphene well and form a dispersion appropriate for specific future applications. In addition, after exfoliation by ultra sonication graphene flakes aggregation due to the van der Waals attractions must be overcome to prepare in long-term stable dispersions of nanometres-size graphene sheets. ; The research has focused on the preparation of stable dispersion ready for transfer without intermediate processes to the Kevlar fabrics. An experimental comparison of the potentials of the 4 solvents for the application resulted in three corresponding to the intended use, two of them examined in detail, supplementing the composition of the LPE liquid medium with triethanolamine to obtain sufficient performance graphene coverage on Kevlar textile fibres.